Nutrition impact symptoms as prognostic indicators in gastric cancer: the role of quality of life and survival outcomes - Liuqing Yang; Qi Zhang; Heping Zhang; Hanping Shi (BMC Cancer)
Abstract Background Nutrition impact symptoms (NIS) are common among cancer patients and influence prognosis. This study aimed to investigate the prognostic significance of NIS in gastric cancer patients using data from the Investigation on Nutrition Status and Clinical Outcome of Common Cancers (INSCOC) database. Methods We conducted a retrospective cohort study using data from 2,673 adult patients with confirmed gastric cancer enrolled in the INSCOC database between January 2013 to February 2020. NIS, including appetite loss, vomiting, dysphagia, and early satiety, were assessed using the Patient-Generated Subjective Global Assessment (PG-SGA). Overall survival (OS) was the primary outcome, while quality of life (QoL) was the secondary outcome. Statistical analyses included Kaplan–Meier survival analysis, Cox proportional hazards regression, and propensity score matching (PSM) to reduce confounding. Results Patients with NIS had significantly worse OS compared to those without (median OS: 74.1 vs. 81.3 months, p < 0.001). In multivariate analysis, NIS was an independent predictor of mortality (HR: 1.28, 95% CI: 1.11–1.48, p = 0.001). Vomiting and dysphagia were particularly associated with increased mortality (HR: 1.22, p = 0.038 and HR: 1.80, p < 0.001, respectively). Interaction analysis revealed that the prognostic impact of NIS was influenced by chemotherapy (P for interaction = 0.002). NIS was also strongly associated with severe malnutrition. Sensitivity analysis confirmed the robustness of these findings, even after excluding short-term mortalities within 180 days. Conclusions NIS are significant independent predictors of poor prognosis in gastric cancer patients, contributing to malnutrition and reduced survival. These findings highlight the importance of early symptom recognition and nutritional intervention to potentially improve outcomes for gastric cancer patients. Trial registration https://www.chictr.org.cn/showproj.html?proj=31813 , identifier ChiCTR1800020329.